Respuesta :

Answer:

Step-by-step explanation:

The LCD here is 4.  Rewrite the entire expression using that denominator:

3x - 2y - 7x - 10

-----------------------

            4

Combining like terms, we get:

 -4x - 2y - 10

---------------------

           4

This can be reduced to  -x - (1/2)y - (10/4).  This has the form Ax + By + C.

Normally, if this were an equation, we'd write Ax + By + C = 0, or, in this particular case,

-x - (1/2)y - (10/4) = 0  or

x + (1/2)y + 10/4 = 0

Answer:

x + (1/2)y + 10/4 = 0

Step-by-step explanation: